Gender equality from the Quranic perspective - Ahmad, Nadzrah; Ishak, Mohd. Haeqal (Penerbit USIM, Universiti Sains Islam Malaysia (USIM), 2018)
Women’s issues existent in the Muslim’s world incurs harsh condemnation from the feminist movements around the globe. They accuse that the oppression and inequality for women originated from the Islamic sources such as the Quranic texts. Muslims on the other hand believe that the Quran presents the best concept of gender equality and inter-relationship for men and women. This study will thus focus on the Quranic concept of gender equality and its suggested dynamic for gender relation. This study aims to broaden the understanding on the Islamic concept of gender equality and its advantages as better alternative to the feminist concept of gender equality. It is a qualitative study that utilizes the deductive and inductive method. Quranic verses pertaining to men’s and women’s equality and relationship will be examined and arranged respectively to the concept it presents. The result indicates that there are several concepts of gender equality in the Quran which can be utilize positively in the present modern gender dynamism.